Preparation method and application of cobalt-based helical superstructure
Patent Information
- Application Number
- CN202410018350.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-05
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-01-05
AI Technical Summary
[0004]本发明要解决手性组装超结构存在手性选择性不高、稳定性不佳、无法控制形貌和尺寸及大规模生产的问题,进而提供一种钴基螺旋超结构的制备方法及应用
[0012]本发明提出了一种简单的水热合成方法来制备钴基螺旋超结构,其具有明显顺时针/逆时针螺旋的手性超结构,手性选择性高,且产品经过超声处理后仍保持稳定形貌,稳定性优异,在基底上可大规模制备且尺寸均匀相同。本发明制备的钴基螺旋超结构具有优异的电催化活性,同时为手性无机纳米材料的设计和组装提供了新方法。
Smart Images

Figure CN117987862B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the preparation method and application of helical superstructures. Background Technology
[0002] Chirality is widespread in nature and plays a crucial role in organisms and life processes. Chiral biomolecules such as amino acids, polypeptides, and proteins are important matrices for asymmetric assembly processes. Through self-assembly, chiral biomolecules can induce inorganic compounds to form chiral superstructures. These chiral superstructures exhibit unique properties that transcend those of individual molecules. Researchers have been dedicated to exploring and developing novel chiral superstructures, which is of great significance to multiple research fields such as chiral optics, chiral recognition, and asymmetric catalysis.
[0003] However, existing chiral assembly structures still have many problems: the chiral selectivity is not high when preparing chiral assembly superstructures; some chiral assembly superstructures are unstable under certain conditions and are prone to dissociation or transformation into other forms; the morphology and size of chiral assembly superstructures cannot be controlled; and the scalability and preparation efficiency need to be improved when preparing chiral assembly superstructures on a large scale. Summary of the Invention
[0004] This invention aims to address the problems of low chiral selectivity, poor stability, inability to control morphology and size, and large-scale production of chiral assembled superstructures, and thus provides a method for preparing cobalt-based helical superstructures and their applications.
[0005] A method for preparing a cobalt-based helical superstructure, comprising the following steps:
[0006] 1. Dissolve hexamethylenetetramine in water to obtain a hexamethylenetetramine solution;
[0007] 2. Add cobalt nitrate to the hexamethylenetetramine solution and stir to dissolve, to obtain a cobalt nitrate / hexamethylenetetramine solution;
[0008] 3. The chiral material is added to a cobalt nitrate / urotropine solution and dissolved by ultrasonication to obtain a mixed solution. The substrate is immersed in the mixed solution and heated to react. After the reaction, it is cooled to room temperature and then ultrasonically vibrated. After vibration, the substrate is removed to obtain the vibrated solution. The vibrated solution is centrifuged to obtain the cobalt-based helical superstructure material.
[0009] The chiral material is D-Cys or L-Cys.
[0010] An application of a cobalt-based helical superstructure for OER electrocatalysis.
[0011] The beneficial effects of this invention are:
[0012] This invention proposes a simple hydrothermal synthesis method to prepare cobalt-based helical superstructures with distinct clockwise / counterclockwise helical chiral structures, high chiral selectivity, and excellent stability after ultrasonic treatment. These superstructures can be fabricated on a large scale with uniform size. The cobalt-based helical superstructures prepared by this invention exhibit excellent electrocatalytic activity and provide a novel method for the design and assembly of chiral inorganic nanomaterials.
[0013] Instruction manual illustrations
[0014] Figure 1 Scanning electron microscope images of L-Cys-Co, D-Cys-Co, and DL-Cys-Co;
[0015] Figure 2 SEM images and particle size distribution diagrams of D-Cys-Co after ultrasonic treatment;
[0016] Figure 3 XPS plot for D-Cys-Co;
[0017] Figure 4 Thermogravimetric comparison diagram of L-Cys-Co and L-Cys;
[0018] Figure 5 The ultraviolet spectra of D-Cys-Co and D-Cys are shown.
[0019] Figure 6 CD spectra of L-Cys-Co and D-Cys-Co;
[0020] Figure 7 CD spectra of L-Cys and D-Cys;
[0021] Figure 8 for Figure 6 G-factor diagrams of L-Cys-Co and D-Cys-Co were obtained by CD spectral calculation;
[0022] Figure 9 The electrocatalytic OER activity of the D-Cys-Co, L-Cys-Co and DL-Cys-Co electrodes prepared in Example 2;
[0023] Figure 10 Tafel curves of the D-Cys-Co, L-Cys-Co and DL-Cys-Co electrodes prepared in Example 2;
[0024] Figure 11 The overpotential diagrams are for the D-Cys-Co, L-Cys-Co, and DL-Cys-Co electrodes prepared in Example 2. Detailed Implementation
[0025] Specific Implementation Method 1: This implementation method is a method for preparing a cobalt-based helical superstructure, which is carried out according to the following steps:
[0026] 1. Dissolve hexamethylenetetramine in water to obtain a hexamethylenetetramine solution;
[0027] 2. Add cobalt nitrate to the hexamethylenetetramine solution and stir to dissolve, to obtain a cobalt nitrate / hexamethylenetetramine solution;
[0028] 3. The chiral material is added to a cobalt nitrate / urotropine solution and dissolved by ultrasonication to obtain a mixed solution. The substrate is immersed in the mixed solution and heated to react. After the reaction, it is cooled to room temperature and then ultrasonically vibrated. After vibration, the substrate is removed to obtain the vibrated solution. The vibrated solution is centrifuged to obtain the cobalt-based helical superstructure material.
[0029] The chiral material is D-Cys or L-Cys.
[0030] The beneficial effects of this embodiment are:
[0031] This embodiment proposes a simple hydrothermal synthesis method to prepare cobalt-based helical superstructures with distinct clockwise / counterclockwise helical chiral structures, high chiral selectivity, and excellent stability after ultrasonic treatment. These superstructures can be fabricated on a large scale with uniform size. The cobalt-based helical superstructures prepared in this embodiment exhibit excellent electrocatalytic activity and provide a novel method for the design and assembly of chiral inorganic nanomaterials.
[0032] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the concentration of the hexamethylenetetramine solution mentioned in step one is 1.8 mg / mL to 4.8 mg / mL. Everything else is the same as in Specific Implementation Method One.
[0033] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that the molar ratio of cobalt nitrate to hexamethylenetetramine in the cobalt nitrate / hexamethylenetetramine solution described in step two is 1:(0.3-0.5). Everything else is the same as in Specific Implementation Method One or Two.
[0034] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that the molar ratio of the chiral material in step three to the cobalt nitrate in the cobalt nitrate / hexamethylenetetramine solution is 1 g:(0.2-0.6) mol. Everything else is the same as in Specific Implementation Methods One to Three.
[0035] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that the ultrasonic dissolution described in step three is specifically performed under conditions of a power of 400W to 800W and a frequency of 40kHz to 45kHz. Everything else is the same as in Specific Implementation Methods One to Four.
[0036] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that the substrate described in step three is a silicon wafer, FTO, or a glass slide. Everything else is the same as in Specific Implementation Methods One to Five.
[0037] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One to Six in that the heating reaction described in step three is specifically carried out at a temperature of 60℃ to 95℃ for 3 to 24 hours. Everything else is the same as in Specific Implementation Methods One to Six.
[0038] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One to Seven in that the ultrasonic oscillation described in step three is specifically performed under the conditions of a power of 300W to 400W and a frequency of 30kHz to 40Hz, with ultrasonic oscillation lasting 10 to 20 minutes. Everything else is the same as in Specific Implementation Methods One to Seven.
[0039] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that the centrifugation separation described in step three is specifically carried out at a rotation speed of 1000 r / min to 8000 r / min for 10 min to 15 min. Everything else is the same as in Specific Implementation Methods One to Eight.
[0040] Specific Implementation Method 10: This implementation method describes the application of a cobalt-based helical superstructure for OER electrocatalysis.
[0041] The beneficial effects of the present invention are verified using the following embodiments:
[0042] Example 1:
[0043] A method for preparing a cobalt-based helical superstructure, comprising the following steps:
[0044] 1. Dissolve hexamethylenetetramine in water to obtain a hexamethylenetetramine solution;
[0045] 2. Add cobalt nitrate to the hexamethylenetetramine solution and stir to dissolve, to obtain a cobalt nitrate / hexamethylenetetramine solution;
[0046] 3. The chiral material was added to a cobalt nitrate / hexamethylenetetramine solution and dissolved by ultrasonication at a power of 400W and a frequency of 40Hz to obtain a mixed solution. The ITO substrate was immersed in the mixed solution and reacted at a temperature of 95℃ for 3 hours. After the reaction, it was cooled to room temperature and then ultrasonically vibrated. After vibration, the substrate was removed to obtain the vibrated solution. The vibrated solution was centrifuged to obtain the cobalt-based helical superstructure material.
[0047] The chiral material is D-Cys or L-Cys.
[0048] The concentration of the hexamethylenetetramine solution mentioned in step one is 2.8 mg / mL.
[0049] In step two, the molar ratio of cobalt nitrate to hexamethylenetetramine in the cobalt nitrate / hexamethylenetetramine solution is 1:0.4.
[0050] The mass ratio of the chiral material described in step three to the molar ratio of cobalt nitrate in the cobalt nitrate / hexamethylenetetramine solution is 1 g: 0.6 mol.
[0051] The ultrasonic oscillation mentioned in step three is specifically performed under the conditions of 400W power and 40Hz frequency, with ultrasonic oscillation for 20 minutes.
[0052] The centrifugation separation described in step three is specifically carried out at a speed of 8000 r / min for 15 min.
[0053] Comparative Experiment: This comparative experiment differs from Example 1 in that DL-Cys is added to the cobalt nitrate / hexamethylenetetramine solution in step three. Everything else is the same as in Example 1.
[0054] Example 1 and comparative experiments: The materials prepared using D-Cys, L-Cys or DL-Cys (products of step 3) were named L-Cys-Co, D-Cys-Co and DL-Cys-Co, respectively.
[0055] Example 2, Electrochemical Measurement (OER):
[0056] Chirality modulates spin states through the so-called chirality-induced spin selectivity (CISS) effect, providing a new paradigm for spin-dependent electrochemistry.
[0057] 1. The bare glassy carbon electrode (GCE) was carefully polished with 0.3 μm and 50 nm alumina slurries until the surface was mirror smooth, then ultrasonicated with deionized water and ethanol, and then dried in air.
[0058] 2. Disperse L-Cys-Co, D-Cys-Co, or DL-Cys-Co into Nafion to obtain a Nafion solution (the ratio of Nafion solution is 10 mg sample, 950 μL ethanol, and 50 μL Nafion). Add 5 μL of Nafion solution to the GCE surface to prepare D-Cys-Co, L-Cys-Co, or DL-Cys-Co electrodes.
[0059] 3. After the D-Cys-Co, L-Cys-Co, or DL-Cys-Co electrodes were dried in air, the electrocatalytic OER activity of the helical superstructure was studied under a standard three-electrode system with a glassy carbon electrode as the working electrode under 1.0 M KOH conditions.
[0060] Figure 1 The images show scanning electron microscope (SEM) images of L-Cys-Co, D-Cys-Co, and DL-Cys-Co. The images reveal a clockwise spiral superstructure D-Cys-Co, a counterclockwise spiral superstructure L-Cys-Co, and a non-spiral superstructure DL-Cys-Co.
[0061] D-Cys-Co was subjected to ultrasonic treatment for 15 minutes at a power of 400W and a frequency of 40Hz. Figure 2 The images show the SEM images and particle size distribution of D-Cys-Co after ultrasonic treatment. As can be seen from the images, the ultrasonic treatment still maintains a stable morphology, and all of them are clockwise spiral superstructures with high chiral selectivity, uniform morphology, and a particle size of about 5.45 micrometers.
[0062] Figure 3 The figure shows the XPS spectra of D-Cys-Co. As can be seen from the figure, the full XPS spectrum confirms the presence of elements such as Co, O, C, N, and S in the helical superstructure.
[0063] Figure 4 The thermogravimetric analysis (TGA) diagrams of L-Cys-Co and L-Cys show that L-Cys-Co exhibits significant weight loss between 200 and 300 °C, which can be attributed to the thermal decomposition of cysteine. The weight percentage of cysteine in the L-Cys-Co helical superstructure was determined to be approximately 50%, indicating that the superstructure of cobalt is induced and involved by cysteine.
[0064] Figure 5 The figures show the UV spectra of D-Cys-Co and D-Cys. As can be seen, the D-Cys-Co helical superstructure exhibits characteristic absorption bands around 286 nm and 360 nm, while pure cysteine shows no absorption. This is because the broad absorption band of Co(III) between 600 and 700 nm facilitates its dd transition, similar to previously reported Co3O4.
[0065] Figure 6 The figures show the CD spectra of L-Cys-Co and D-Cys-Co. As can be seen from the figures, the D-Cys-Co helical superstructure exhibits a significant thermal response, with five positive and negative peaks at 286 nm, 360 nm, 500 nm, 552 nm, and 678 nm. This differs from the CD signal of D-Cys at 204 nm. Figure 7 Furthermore, L-Cys-Co and D-Cys-Co have opposite configurations but the same elution positions. The CD signal of the chiral superstructure is significantly different from that of chiral cobalt oxide nanoparticles synthesized using the same cysteine ligand, indicating the influence of the helical superstructure on chiral reactions.
[0066] Figure 7The figure shows the CD spectra of L-Cys and D-Cys. As can be seen from the figure, the spectral positions of the CD peaks of L-Cys and D-Cys are almost completely aligned with the absorption peaks. The helical superstructure synthesized by L- and D-Cys ligands shows a perfect mirror-symmetric CD signal with almost overlapping peak positions.
[0067] Figure 8 for Figure 6 CD spectroscopy calculations yielded G-factor diagrams for L-Cys-Co and D-Cys-Co. The diagrams show that the anisotropy g-factor of the D-Cys-Co helical superstructure at 678 nm is 0.0027, indicating that it has strong tropical activity.
[0068] Figure 9 The electrocatalytic OER activities of the D-Cys-Co, L-Cys-Co, and DL-Cys-Co electrodes prepared in Example 2 are shown. From the polarization curves, both D-Cys-Co and L-Cys-Co exhibit higher water oxidation current densities than the achiral DL-Cys-Co.
[0069] Figure 10 The image shows the Tafel curves of the D-Cys-Co, L-Cys-Co, and DL-Cys-Co electrodes prepared in Example 2. As can be seen from the figure, the Tafel slopes of D-Cys-Co and L-Cys-Co are 85.3 mV dec. -1 Less than 136.8 mVdec of DL-Cys-Co -1 This indicates that it is more favorable to OER dynamics.
[0070] Figure 11 The overpotential diagrams are for the D-Cys-Co, L-Cys-Co, and DL-Cys-Co electrodes prepared in Example 2; the chiral D-type and L-type catalysts at 10 mA / cm² are shown. -2 The overpotentials at 30 mA cm⁻¹ were 320 mV and 310 mV, respectively. -2 The overpotentials at 50 mA cm⁻¹ were 370 mV and 360 mV, respectively. -2 The overpotentials at these times were 410 mV and 390 mV, respectively. However, at 10 mA / cm²... -2 30mAcm -2 and 50mAcm -2 At these values, the values of the achiral DL-Cys-Co increased to 350 mV, 450 mV, and 520 mV, respectively. These results indicate that chiral enhancement has a significant enhancing effect on the OER activity in chiral superstructures.
Claims
1. A method for preparing a cobalt-based helical superstructure, characterized in that... It is done in the following steps:
1. Dissolve hexamethylenetetramine in water to obtain a hexamethylenetetramine solution; 2. Add cobalt nitrate to the hexamethylenetetramine solution and stir to dissolve, to obtain a cobalt nitrate / hexamethylenetetramine solution; 3. The chiral material is added to a cobalt nitrate / urotropine solution and dissolved by ultrasonication to obtain a mixed solution. The substrate is immersed in the mixed solution and heated to react. After the reaction, it is cooled to room temperature and then ultrasonically vibrated. After vibration, the substrate is removed to obtain the vibrated solution. The vibrated solution is centrifuged to obtain the cobalt-based helical superstructure material. The chiral material is D-Cys or L-Cys.
2. The method for preparing a cobalt-based helical superstructure according to claim 1, characterized in that... The concentration of the hexamethylenetetramine solution mentioned in step one is 1.8 mg / mL to 4.8 mg / mL.
3. The method for preparing a cobalt-based helical superstructure according to claim 1, characterized in that... In step two, the molar ratio of cobalt nitrate to hexamethylenetetramine in the cobalt nitrate / hexamethylenetetramine solution is 1:(0.3-0.5).
4. The method for preparing a cobalt-based helical superstructure according to claim 1, characterized in that... The mass ratio of the chiral material described in step three to the molar ratio of cobalt nitrate in the cobalt nitrate / hexamethylenetetramine solution is 1 g:(0.2-0.6) mol.
5. The method for preparing a cobalt-based helical superstructure according to claim 1, characterized in that... The ultrasonic dissolution described in step three is specifically performed under conditions of a power of 400W to 800W and a frequency of 40kHz to 45kHz.
6. The method for preparing a cobalt-based helical superstructure according to claim 1, characterized in that... The substrate mentioned in step three is a silicon wafer, FTO, or a glass slide.
7. The method for preparing a cobalt-based helical superstructure according to claim 1, characterized in that... The heating reaction described in step three is specifically carried out at a temperature of 60℃ to 95℃ for 3 to 24 hours.
8. The method for preparing a cobalt-based helical superstructure according to claim 1, characterized in that... The ultrasonic oscillation mentioned in step three is specifically performed under the conditions of a power of 300W to 400W and a frequency of 30kHz to 40Hz for 10 to 20 minutes.
9. The method for preparing a cobalt-based helical superstructure according to claim 1, characterized in that... The centrifugation separation described in step three is specifically carried out at a speed of 1000 r / min to 8000 r / min for 10 min to 15 min.
10. The application of the cobalt-based helical superstructure prepared according to claim 1, characterized in that... It is used for OER electrocatalysis.
Citation Information
Patent Citations
Chiral cobalt-nickel bimetallic electrocatalyst with high spin polarizability, catalytic electrode and preparation method and application thereof
CN122303938A